High-intensity interval training in judo uchi-komi. Fundamentals and practical recommendations - Franchini, E. (The Arts and Sciences of Judo, 2021)
Judo is characterised by high-intensity actions (e.g., attacks, defensive actions and counter-attacks, in both standing and ground positions), interspersed with low-intensity actions (e.g., displacement without contact) or pause (e.g., referee stoppage), resulting in an intermittent activity. Thus, high-intensity interval training (HIIT) is part of judo-specific training and used as complementary training. Consequently, a proper HIIT prescription can benefit high-level judo athletes. Indeed, a recent systematic review (Franchini et al., 2019a) reported that HIIT was able to improve the aerobic and anaerobic fitness of combat sport athletes, including judo athletes, while maintaining athletes` body mass. HIIT can be divided into four main protocols: HIIT short-intervals, HIIT long-intervals, repeated sprint training (RST) and sprint interval training (SIT) (Buchheit and Laursen, 2013a and b). The assessment of physiological indexes (intensity associated with the maximal blood lactate steady state, maximal oxygen consumption, and maximal sprint) or of time-motion variables (high-intensity actions, low-intensity actions, effort-pause ratio) are key elements for a better prescription of each of these four HIIT protocols and to a better individualisation of the training loads imposed on the athletes (Buchheit and Laursen, 2013a and b; Julio et al., 2019). During judo training sessions, uchi-komi (technique repetition without throwing the opponent) is one of the most-executed exercises by high-level judo athletes (Franchini & Takito, 2014). Thus, this article presents a proposal for HIIT prescription for judo athletes, exemplifying with different HIIT protocols (HIIT short-intervals, HIIT long-intervals, RST, SIT, and based on judo-specific time-motion), using uchi-komi as the exercise mode and the parameters for the individualisation of these protocols.